The development and evaluation of a second-order factor structure for the Leadership Behaviour Inventory (LBI) - Solomon, Nikki (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MComm (Industrial Psychology))--University of Stellenbosch, 2006.